‘High hopes for treatment’: Australian stakeholder perspectives of the clinical translation of advanced neurotherapeutics for rare neurological diseases - Christina Q. Nguyen; Didu S. T. Kariyawasam; Tsz Shun Jason Ngai; James Nguyen; Kristine Alba‐Concepcion; Sarah E. Grattan; Elizabeth E. Palmer; Kate Hetherington; Claire E. Wakefield; Russell C. Dale; Sue Woolfenden; Shekeeb Mohammad; et al. (Health Expectations)
Abstract Introduction Advanced therapies offer unprecedented opportunities for treating rare neurological disorders (RNDs) in children. However, health literacy, perceptions and understanding of novel therapies need elucidation across the RND community. This study explored healthcare professionals' and carers' perspectives of advanced therapies in childhood‐onset RNDs. Methods In this mixed‐methodology cross‐sectional study, 20 healthcare professionals (clinicians, genetic counsellors and scientists) and 20 carers completed qualitative semistructured interviews and custom‐designed surveys. Carers undertook validated psychosocial questionnaires. Thematic and quantitative data analysis followed. Results Participants described high positive interest in advanced therapies, but low knowledge of, and access to, reliable information. The substantial ‘therapeutic gap’ and ‘therapeutic odyssey’ common to RNDs were recognised in five key themes: (i) unmet need and urgency for access; (ii) seeking information; (iii) access, equity and sustainability; (iv) a multidisciplinary and integrated approach to care and support and (v) difficult decision‐making. Participants were motivated to intensify RND clinical trial activity and access to advanced therapies; however, concerns around informed consent, first‐in‐human trials and clinical trial procedures were evident. There was high‐risk tolerance despite substantial uncertainties and knowledge gaps. RNDs with high mortality, increased functional burdens and no alternative therapies were consistently prioritised for the development of advanced therapies. However, little consensus existed on prioritisation to treatment access. Conclusions This study highlights the need to increase clinician and health system readiness for the clinical translation of advanced therapeutics for RNDs. Co‐development and use of educational and psychosocial resources to support clinical decision‐making, set therapeutic expectations and promotion of equitable, effective and safe delivery of advanced therapies are essential. Patient or Public Contribution Participant insights into the psychosocial burden and information need to enhance the delivery of care in this formative study are informing ongoing partnerships with families, including co‐production and dissemination of psychoeducational resources featuring their voices hosted on the Sydney Children's Hospitals Network website SCHN Brain-Aid Resources.